STRUKTUR KOMUNITAS, PERANAN DAN ADAPTASI MAKROALGA DI INTERTIDAL BERBATU - Tri Handayani (OSEANA, 2020)
Rocky shore intertidal occurs at the interface of the land and sea, which regularly exposed with tidal waves. In general, rocky shore intertidal is influenced by extreme physical factors, so organisms need to adapt well. Macroalgae on rocky shore intertidal are mostly macroalgae that have epilithic life foam, for example, Sargassum, Turbinaria, Hypnea, Gracilaria, Amphiroa, Chaetomorpha, Ulva, Acanthophora, and Gelidium. The role of macroalgae on rocky shore intertidal are as a primary producer/primary productivity, food for other organisms (fish, mollusc, sea urchin, crab), nursery ground for other organisms (fish, sea urchin, sea cucumber, and crab), and provide shelter for benthic fauna (crabs, sea urchin, molluscs, polychaeta and sea star). The adaptation of macroalgae on rocky shore intertidal was through morphological changes. Gracilaria salicornia on rocky shore intertidal has slimmer thallus than G. salicornia on non-rocky shore intertidal.